OPPORTUNITIES AND CHALLENGES OF ORGANIZING AND IMPLEMENTING DISTANCE PRE-SCHOOL EDUCATION: TEACHERS’ OPINIONS - Braslauskienė, Rasa; Jacynė, Reda; Norviliene, Aida; Ramanauskienė, Sada; Strazdienė, Neringa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The Council of the European Union (2020) points out that the COVID-19 pandemic has had a major impact on education and teaching systems and has fundamentally changed the way we learn, teach, communicate and collaborate within and between our education and teaching communities. The aim of this study is to explore the opinion of pre-school teachers on the opportunities and challenges faced by them in organizing and conducting pre-school education at a distance. The strategy of qualitative research was chosen for the study, Klaipėda city pre-school education teachers were interviewed. The study revealed that teachers did not change the content of education programs, sought to maintain the continuity of education and develop all the competencies of preschool children. Various digital and technical tools for distance education were used. Participants of the educational process experienced a variety of emotions and disturbances. Teachers missed for more decisive action of the institution’s administration. The opinion of educators discovered during the research helped to highlight advantages and disadvantages of distance pre-school education.